Review The Human Future: Artificial Humans and Evolution in Anglophone Science Fiction of the 20th Century by Stefan Lampadius - Torres Romero, María (Miscelánea: A Journal of English and American Studies, 2023)
Review of The Human Future: Artificial Humans and Evolution in Anglophone Science Fiction of the 20th Century by Stefan Lampadius.